Antivirals for influenza: a summary of a systematic review and meta‐analysis of observational studies. (27th August 2013) - Santesso, Nancy; Hsu, Jonathan; Mustafa, Reem; Brozek, Jan; Chen, Yao Long; Hopkins, Jessica P.; Cheung, Adrienne; Hovhannisyan, Gayane; Ivanova, Liudmila; Flottorp, Signe A.; Sæterdal, Ingvil; Wong, Arthur D.; et al.
Abstract : Despite the use of antivirals to treat patients with severe influenza, questions remain with respect to effects and safety. Although a recent systematic review has provided some indication of benefit, the analysis is limited by the quality of the available evidence from randomized controlled trials. To supplement the existing information, the authors conducted a systematic review of observational studies of antiviral treatment for influenza. This report summarises the findings of that review. Similar to the randomised trials, the confidence in the estimates of the effects for decision‐making is low to very low primarily due to the risk of selection and publication bias in the observational studies. From these observational studies, the summary estimates suggest that oseltamivir may reduce mortality, hospitalisation and duration of symptoms compared with no treatment. Inhaled zanamivir may also reduce symptom duration and hospitalisations, but patients may experience more complications compared with no treatment. Earlier treatment with antivirals is generally associated with better outcomes than later treatment. Further high‐quality evidence is needed to inform treatment guidelines because of the overall low to very low quality of evidence.